2017
DOI: 10.1515/boku-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Germination characteristic of Silphium perfoliatum L. seeds

Abstract: SummarySilphium perfoliatum L. is a perennial and flowering crop that has been investigated in recent years for its potential as an energy plant, particularly for biogas production. A stand establishment by sowing of seeds is complicated, owing to the low germination capacity of untreated S. perfoliatum L. seeds. Consequently, germination experiments were carried out with two-to four-factor levels to determine the effect of selected factors (medium, pretreatment, light, temperature, prechilling) on dormancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Using a screening machine with a set of rounded hole sieves (8.5 mm), followed by elongated hole sieves (3 mm and 1.5 mm) and a weight reader, and resulted in a minimum seed viability of 97.5%, filtering about 50% of the starting material at the end of the process. Gansberger et al [101], emphasized the need to treat S. perfoliatum seeds to increase germination and observed the positive effects of gibberellic acid, alternating light, and temperature regimes (12 h at 20/30 • C), and chilling to enhance germination capacity.…”
Section: Establishment By Sowingmentioning
confidence: 99%
“…Using a screening machine with a set of rounded hole sieves (8.5 mm), followed by elongated hole sieves (3 mm and 1.5 mm) and a weight reader, and resulted in a minimum seed viability of 97.5%, filtering about 50% of the starting material at the end of the process. Gansberger et al [101], emphasized the need to treat S. perfoliatum seeds to increase germination and observed the positive effects of gibberellic acid, alternating light, and temperature regimes (12 h at 20/30 • C), and chilling to enhance germination capacity.…”
Section: Establishment By Sowingmentioning
confidence: 99%
“…The germination capacity can be considerably increased when seeds are pretreated with a chemical solution (GA 3 and KNO 3 ) rather than only supplied with water for germination. The same study found that the best germination was achieved when a dark-light cycle (12:12) was applied with a temperature alternating between 20 and 30 • C, preceded by wet stratification, for seven days, at 0 • C [12]. Even though it is recommended to plant Silphium by using seedlings, to reduce costs, the planting by sowing can also be used.…”
Section: Description and Originmentioning
confidence: 99%
“…Several studies have analyzed the best conditions for growing Silphium perfoliatum as feedstock for biogas production [11,12,103]. It is also seen as a promising alternative substrate for silage maize, due to its reduced agricultural requirements, which enable it to be grown on marginal or less productive soil [16].…”
Section: Utilization and Benefits/advantages Of Silphium Perfoliatummentioning
confidence: 99%
“…No problems with seed germination and emergence were observed. Schäfer et al [28] in Germany, and Gansberger et al [29] in Austria, emphasize the importance of seed quality and uniformity of seeds, because Silphium produces heterogeneous seeds with varying degrees of maturity with low germination capacity due to the extended ripening phase.…”
Section: Plant Densitymentioning
confidence: 99%